Political Prisoners and the Irish Conflict 100 Years On. (11th October 2021) - BRYSON, ANNA; McEVOY, KIERAN; ALBERT, ALLELY
Abstract: This article traces the impact of Irish political prisoners on the prison landscape in Ireland, north and south, over the past 100 years. For the post‐1969 period in Northern Ireland, it explores three different styles of prison management: reactive containment, criminalisation, and managerialism. It also examines the ways in which political prisoners sought to resist, including through strategic use of law, dirty protests and hunger strikes, escapes and the use of violence. The article then discusses the early release of prisoners under the Good Friday Agreement and the role that ex‐prisoners have played in the peace process. It concludes with some reflections on the ongoing tensions between the state and dissident republican prisoners, asking what lessons (if any) can be gleaned from the past 100 years.